1997
DOI: 10.1002/(sici)1097-0142(19970815)80:4<725::aid-cncr11>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for breast carcinoma in Singaporean Chinese women

Abstract: METHODS.A forward stepwise logistic regression model adjusted for confounding variables of age, age at menarche, menopausal status, parity, age at first and last Breast Service, Singapore Cancer Center and delivery, use of oral contraceptives, hormone replacement therapy, family history Department of Surgery, Singapore General Hosof breast carcinoma, history of benign breast biopsy, smoking history, height, pital, Singapore, Republic of Singapore.weight, body mass index, and waist to hip ratio was used. RESULT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 28 publications
4
47
2
Order By: Relevance
“…Data from the present study confirm previous findings that the relationship between anthropometric measures of adiposity and breast cancer risk was modified by menopausal status, with higher BMI, waist circumference, and WHR associated with increased risk for postmenopausal women (Ng et al 1997, Huang et al 1999, Shu et al 2001, Morimoto et al 2002, Harvie et al 2003, Lahmann et al 2004, Modugno et al 2006, Rinaldi et al 2006. The possible biological mechanism underlying excess adiposity and postmenopausal breast cancer risk is that increased adiposity tends to be associated with higher circulating levels of estrogens through greater peripheral conversion of androgens to estrogens by aromatase in adipose tissue among postmenopausal obese women (Silteri 1987, Potischman et al 1996.…”
Section: Discussionsupporting
confidence: 90%
“…Data from the present study confirm previous findings that the relationship between anthropometric measures of adiposity and breast cancer risk was modified by menopausal status, with higher BMI, waist circumference, and WHR associated with increased risk for postmenopausal women (Ng et al 1997, Huang et al 1999, Shu et al 2001, Morimoto et al 2002, Harvie et al 2003, Lahmann et al 2004, Modugno et al 2006, Rinaldi et al 2006. The possible biological mechanism underlying excess adiposity and postmenopausal breast cancer risk is that increased adiposity tends to be associated with higher circulating levels of estrogens through greater peripheral conversion of androgens to estrogens by aromatase in adipose tissue among postmenopausal obese women (Silteri 1987, Potischman et al 1996.…”
Section: Discussionsupporting
confidence: 90%
“…This could be due to the fact that BMI does not allow for variations in the lean-to-fat mass proportion in the body, while especially waist circumference correlates with the amount of abdominal (visceral and subcutaneous) fat [26][27][28] --the adipose tissue component most strongly associated with insulin resistance, hyperinsulinemia and lower SHBG. On the other hand, in the current study, as in some, 29,30 but not all, 31 previous prospective studies, no association with breast cancer risk was found for WHR, an index of the relative accumulation of abdominal compared to gluteal fat. In our study, waist and hip circumferences were both highly related to risk, and also highly correlated to each other, so that calculating the ratio between the 2 measures could have attenuated the associations with cancer risk.…”
Section: Discussioncontrasting
confidence: 61%
“…Late age at first FTP is an independent risk factor for 'postmenopausal women' and a moderate risk factor of breast cancer for premenopausal women that is consistent with the findings from other studies (Helmrich et al, 1983;Ng et al, 1997;Tung et al, 1999;Sasaki et al 1995). A history of early menarche (below age 13) was surprisingly observed to be protective for all women but the protection from early menarche was not observed to be statistically significant in the separate analysis of premenopausal and postmenopausal women in this study.…”
Section: Resultssupporting
confidence: 90%